Suppression of Reactive Power in Isolated Modular Multilevel DC–DC Converter Under Quasi Square-Wave Modulation - Changjiang Sun; Xu Cai; Jianwen Zhang; Gang Shi (IEEE Access, 2019)
An isolated modular multilevel dc-dc converter (IMMDCC) consisting of two modular multilevel converters (MMCs) coupled via a medium-frequency transformer is competitive for medium- and high-voltage applications because of its high modularity and high-voltage handling capability. Employing the quasi square-wave modulation (QSM) scheme for MMCs of the converter can increase the dc-link voltage utilization ratio and realize soft-switching operation, compared with sinusoidal wave modulation methods. However, the accurate reactive power control at the ac side of the IMMDCC can hardly be achieved under the QSM mode. The ac-side reactive power and current stress increase considerably when the conversion ratio deviates from the transformer turn ratio. In order to address this issue, this paper presents an arm voltage decoupling control scheme for the IMMDCC by introducing a virtual buck/boost conversion stage between the dc-side voltage and the transformer voltage. The transformer primary and secondary voltages are kept matched to suppress the reactive power when the dc-side voltage varies. The theoretical analysis shows that the proposed control enhances the power transfer capability and reduces the ac-side current stress of the IMMDCC. In addition, submodule voltages are maintained even when the dc voltages exceed the designed value under the conventional control scheme, which implies that the voltage range of the converter is expanded. The simulation and experimental results confirm the effectiveness of the proposed modulation and control strategy.